FORAGE PRODUCTIVITY OF ARBILA (Phaseolus lunatus) AT VARIOUS LEVELS OF RHIZOBIUM INOCULANTS AND HARVESTING TIMES - Koten, B.B.; Soetrisno, R.D.; Ngadiyono, N.; Soewignyo, B. (Diponegoro University, 2012)
The study was conducted to evaluate forage productivity of arbila (Phaseolus lunatus) as theruminant feed at various levels of rhizobium inoculants and harvesting times, was designed followingcompletely randomized design of factorial pattern with two factors. The first factor was the level ofinoculums (I) i.e. I1 (without inoculum), I2 (5 g/kg seed), I3 (10 g/kg seed), and I4 (15 g/kg seed). Thesecond factor was harvesting time (U) i.e. U1 (60 days), U2 (80 days), U3 (100 days) with 4replications. The variables were N uptake, production of dry matter (DM) and organic matter (OM), andpercentage of OM, crude protein (CP), crude fiber (CF), nitrogen free extract (NFE), extract ether (EE)and ash of arbila forage (based on DM). The results showed that inoculant treatment at the rate of 15g/kg seed produced the highest percentage of effective nodules (98.72%), and in combination withharvesting age at 100 days each polybag of plant was able to absorb the higest amount of N (688. 10 g)with production of DM 273.81 g, OM production 263.96 g and nutrients content based on DM of about91.14% OM, 33.52% CF, 34.76%, 5.75% EE, 09.37% ash, and 16.16% CP. From the study, it can beconcluded that arbila plants inoculated specific rhizobium Phaseolus vulgaris at the rate of 15 g/kg seedand harvested at 100 days yielded the best forage as feed.